The Influence of Compensation, Environment, Determination and Characteristic of Employees to Performance of Employees in PT Baruna Nusantara Eka - . Qodaria (Accounthink, 2016)
This research aims to know to what extend the influence on compensation, environment, determination and characteristic of employees to toward their performance at PT. Baruna Nusantara Eka. The objects of this research are the employees of PT. Baruna Nusantara Eka in collecting the sample, this research used method of slovin formula, with the error sampling at 10%, of 75 employees. The data is collected through questionnaire distributed to PT. Baruna Nusantara Eka Perkasa employees. The data has been validated and realibility test before being analyzed.  The analysis technique used in this research is double regression. The result shows that compensation, environment and characteristic of employees does not influence the performance, meanwhile the determination significantly influence in simultaneous test, compensation, environment, determination and characteristic of employees influence significantly.